Transient Neurological Attacks in the General Population: Prevalence, Risk Factors, and Clinical Relevance - Bots, Michiel L.; van der Wilk, Eline C.; Koudstaal, Peter J.; Hofman, Albert; Grobbee, Diederick E. (Stroke (1970), 1997)
Background and Purpose Patients with typical transient ischemic attacks (TIAs) have a higher risk of stroke but a lower risk of cardiac events than patients with nonspecific transient neurological symptoms. We assessed the prevalences of typical TIAs and nonspecific transient neurological attacks (TNAs) and their determinants in the general population because such data are virtually absent. Methods The Rotterdam Study is a population-based cohort study of 7983 subjects, aged 55 years and over, conducted in a district of Rotterdam, the Netherlands. At baseline examination, a history of episodes of disturbances in sensibility, strength, speech, and vision that lasted less than 24 hours and occurred within the preceding 3 years was determined by a trained physician. When such a history was present, information on time of onset, duration, and disappearance of symptoms and a detailed description of the symptoms (in ordinary language) were obtained. Subjects were classified by a neurologist as typical TIA or nonspecific TNA. Results Prevalence of TNAs was 1.9% in subjects aged 55 to 64 years, 3.5% in subjects aged 65 to 74 years, 4.3% in subjects aged 75 to 84 years, and 5.1% in subjects aged 85 years or over. Prevalence figures for typical TIA were 0.9%, 1.7%, 2.3%, and 2.2% and for nonspecific TNA 1.0%, 1.8%, 2.0%, and 2.9%, respectively. Clinical parameters such as number of attacks, onset, duration, and disappearance of symptoms were similar for typical TIA and nonspecific TNA. Increased age, male sex, diabetes mellitus, low HDL cholesterol, Q-wave myocardial infarction on electrocardiogram, and carotid atherosclerosis were related to typical TIA, whereas increased age, hypertension, low HDL cholesterol, smoking, and angina pectoris were associated with nonspecific TNA. Conclusions About half of the subjects with a TNA had symptoms that were not entirely typical for a TIA. Differences in associations with risk factors between typical TIA and nonspecific TNA point toward different underlying mechanisms of symptoms and may lead to different ancillary investigations and possibly treatment.